Ensino de programação para alunos do ensino básico: um levantamento das pesquisas realizadas no Brasil - Silva, Jailson Cunha da (2017)
In this article we present the results of a literature review on the strategies used and content selected for teaching programming in basic education in Brazil. The articles published in the last five years (2012-2016)of investigated in two events and a national journal of the area, being the Brazilian Symposium on Informatics in Education (SBIE), Teaching Workshop on Computational Thinking, Algorithm and Programming (WAlgProg) And the Brazilian Journal of Informatics in Education (RBIE). The most used tool was the Scratch language, had some articles that presented the concepts of computation integrated with content of disciplines of the basic education curriculum.